Rancang Bangun Sistem Klasifikasi Tipe Permukaan Jalan menggunakan Gray Level Co-Occurrence Matrix (GLCM) dan Support Vector Machine (SVM) berbasis Raspberry Pi - Akbar Wira Bramantya; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Roads are a pathways made to facilitate traffic access from one place to another. Indonesia has a roads as far as 537.838 km. However, all of these road didn't have same condition, there are still many road in bad condition. On the other side, our current transportation is just evolve to the Smart Car era, where this technology focuses on autonomous driving systems and driver safety. Therefore, needed a system that can overcome these various road conditions. So, in this research will do a testing using Gray Level Co-Occurrence Matrix (GLCM) and Support Vector Machine (SVM) to classify the roads are in asphalt condition, rocky condition, or paved condition. The GLCM feature used in this research is the best 4 features from total 6 features to be tested namely dissimilarity, correlation, homogeneity, contrast, ASM, and energy. This test is started using SVM linear kernel, polynomial kernel, and RBF kernel, the value of d = 1, and value of Î¸ = 0o, 45o, 90o, 135o. After all of these tests, the best result were obtained. They are GLCM using dissimilarity, correlation, contrast, and energy features, the value of d = 1, and combination from all of angles, angle 0o, 45o, 90o, 135o simultaneously also for SVM using linear kernel. The accuracy obtained from this combination reaches 97% in SVM training set and 98,3% in manual testing using test data. System integration testing using camera input got 88,6% in accuracy and system integration testing on electric motors performance got 87% in accuracy.